Košarka, igra za različne generacije - Sirnik, Matic (Šport (Ljubljana), 2024)
Basketball is a popular sport in Slovenia, which includes various forms such as 5:5 and 3:3. It is played on relatively small courts, requiring high-intensity movements, the most common of which are changes in movement direction, accelerations and stops. In addition to maintaining and developing motor skills such as coordination, speed and endurance, basketball also promotes social skills, cooperation and tactical thinking. In Slovenia, official competitions are organised for all age groups. Recreational basketball is also very popular, especially among adults who do not take part in organised competitions. Basketball can make a positive contribution to a person's physical and mental health, but it is important that the exercise is tailored to the individual's fitness, health and age.
Keywords: basketball; gibalna dejavnost; health; košarka; physical activvity; sport; šport; zdravje